2005
DOI: 10.1111/j.0022-1112.2005.00668.x
|View full text |Cite
|
Sign up to set email alerts
|

American paddlefish leukocytes demonstrate mammalian‐like cytochemical staining characteristics in lymphoid tissues

Abstract: American paddlefish Polyodon spathula leukocytes demonstrated cytoplasmic staining patterns very similar to mammalian leukocytes when stained with acid phosphatase, a-naphthyl butyrate esterase and b-glucuronidase. American paddlefish monocytes, lymphocytes and granulocytes stained positive for acid phosphatase. Monocytes stained positive for a-naphthyl butyrate esterase. Lymphocytes that stained positive for a-naphthyl butyrate esterase were designated type A. Lymphocytes that stained positive with antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 34 publications
1
26
0
Order By: Relevance
“…Histologically, the thymus is lobulated and organised in the outer cortex enclosing the central medulla (Petrie-Hanson and Peterman 2005). A diversity of different cell types is found within the thymus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Histologically, the thymus is lobulated and organised in the outer cortex enclosing the central medulla (Petrie-Hanson and Peterman 2005). A diversity of different cell types is found within the thymus.…”
mentioning
confidence: 99%
“…The cortex is predominantly composed of closely packed lymphocytes. The medulla is composed of sparsely organised lymphocytes, macrophages, reticular cells and Hassall's corpuscles that have a disperse distribution (Fange 1986;Petrie-Hanson and Peterman 2005;Peterman and Petrie-Hanson 2006). …”
mentioning
confidence: 99%
“…There are minimal histological differences between vertebrate thymus. The juvenile paddlefish thymus is lobulated and differentiated into cortical and medullary areas (Petrie‐Hanson & Peterman, 2005), as is the condition in the sturgeon (Fange, 1986), elasmobranchs (Zapata & Cooper, 1990), and mammals (Burkitt et al ., 1993). In other fishes, however, the thymus is not lobulated.…”
Section: Discussionmentioning
confidence: 99%
“…In other fishes, however, the thymus is not lobulated. Hassall’s bodies were not observed in the paddlefish thymus viewed in this study, but have been reported in light microscopy studies of thymic tissues from older paddlefish (Good et al ., 1966; Petrie‐Hanson & Peterman, 2005). In the elasmobranch thymus, epithelial cells containing masses of degenerated fibrous material resembling the keratin bundles found in the unicellular Hassall’s bodies of mammalian thymus have been observed (Zapata et al ., 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation